Papers - - Production - Foreign - Oil and Gas Development in France and Northern Africa - H. De Cizancourt (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1934)
Peche1bronn.—So far Pechelbronn is the only producing district. Figures are given in Table 2 covering the main features of the field, but these figures call for the following remarks: First, Pechelbronn should not' be considered as a single unit, it appears, but as a succession of small oil fields, each of which is affected by very variable conditions. Consequently, certain figures concerning production per acre, production per acre-foot, pressure conditions and thicknesses of oil sands would be so misleading that they have been omitted here. Second, as regards production methods, attention is drawn especially to the fact that 42 per cent of the oil is extracted by the use of shafts and galleries and the remainder by pumping wells. Exploitation, formerly confined to Oligocene sands, has been extended recently to Jurassic and Triassic oil-bearing formations. Gabian.—This small oil field, discovered in 1924, is almost exhausted. Exploitation to date is restricted to three wells. There were no drilling activities in 1933. Exploration.—During 1933, two exploration holes have been started in France. The first, in the vicinity of Lavelanet (Ariége) on the Dreuille anticline, has reached the depth of 2400 ft,.; the second, in the Autun Permian Basin, is drilling at 1300 feet. Northern Africa Morocco.—Drilling operations have been on a large scale in Morocco. In the Gharb district (Souk el Arba area), the deepest well was abandoned in 1933 at 7014 ft. Small irregular productive horizons were encountered in the Miocene at shallow depth, oil and gas showing in the Eocene, but no commercial oil field has been discovered. In the Djebel Tselfat, near Petitjean, a small production of oil was obtained from a Jurassic horizon. In the meantime deeper formations are being explored and a new structure in the vicinity is being tested. In Eastern Morocco, a well is drilling near Taza. Production in Morocco, about 2400 bbl., has not been listed on Table 2, owing to its origin—exploration wells.